1980
DOI: 10.1172/jci109963
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Function in a Uremic Rat Model

Abstract: A B S T R A C T The main objective of this study was to determine whether the principal abnormality of thyroid function observed in patients with chronic renal failure, low serum triiodothyronine (T3) concentration, causes hypothyroidism at the tissue level. A partially nephrectomized (Nx) uremic rat model was developed and the following parameters of thyroid function were assessed: serum total thyroxine (TT4), total T3 (TT3), and thyrotropin and liver T3 content, and activity oftwo thyroid hormone-dependent e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

1983
1983
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(12 citation statements)
references
References 34 publications
0
11
1
Order By: Relevance
“…Moreover, analysis of covariance established that only for one spot, spot 8, could the differences between groups be accounted for by food intake alone. The possibility that the genomic alterations were due to a lowering of circulating T3 was explored in view of previous reports by Lim et al suggesting that subtotal nephrectomy results not only in a lower circulating T3 but also in diminished activity of hepatic a-GPD and ME (5). These authors, therefore, proposed that the nephrectomized animal was a potentially useful model of the clinical "low T3 syndrome" that characterizes many chronic illnesses in man (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, analysis of covariance established that only for one spot, spot 8, could the differences between groups be accounted for by food intake alone. The possibility that the genomic alterations were due to a lowering of circulating T3 was explored in view of previous reports by Lim et al suggesting that subtotal nephrectomy results not only in a lower circulating T3 but also in diminished activity of hepatic a-GPD and ME (5). These authors, therefore, proposed that the nephrectomized animal was a potentially useful model of the clinical "low T3 syndrome" that characterizes many chronic illnesses in man (24).…”
Section: Discussionmentioning
confidence: 99%
“…This model was of special interest to us since the decreased food intake and growth retardation that accompany it reflect similar phenomena in the clinical uremic syndrome (4). Moreover, a recent report by Lim et al (5) indicates that the level of circulating triiodothyronine (T3)1 is reduced in the chronically partially ne-phrectomized rat, as has been observed in azotemic man (6). This report also suggested that in the rat model the reduction in circulating T3 leads to tissue hypothyroidism, as reflected by reduced activities of hepatic alpha-glycerolphosphate dehydrogenase (a-GPD) and malic enzyme (ME).…”
mentioning
confidence: 89%
“…Plasma was obtained by centrifugation (2500 ϫ g, 10 min, 4°C) and red cells were washed twice prior to being resuspended to the original volume in NaCl (0.9%). Livers were perfused in situ with chilled 0.15 M KCl and hepatic microsomes were prepared by the method of Lim et al [16]. Plasma and the remaining liver tissue were immediately snap frozen in liquid nitrogen and stored at Ϫ70°C.…”
Section: Animals and Dietsmentioning
confidence: 99%
“…It would be of considerable interest, therefore, to test the adequacy of this assumption by analyzing the mRNA profile in animal models of nonthyroidal disease such as the tumor-bearing rat (45) and the uremic rat (46). Such studies could conceivably APPENDIX Table I, when nuclear sites are fully saturated by injected T3 for the first day, the necessary but not sufficient (compatible) criteria require that the value at the end of the first day of starvation in euthyroid animals treated with T3, (ES,)', should equal or exceed the value in the euthyroid fed animal EF.…”
Section: Discussionmentioning
confidence: 99%